Schreiben auf statuarischen Monumenten Aspekte materialer Textkultur in archaischer und frühklassischer Zeit - Dietrich, Nikolaus (Materiale Textkulturen, 2020)
The series Material Text Cultures is the publication organ of the Collaborative Research Center 933 of the same name at Heidelberg University, funded by the German Research Foundation (DFG). The series publishes collections and monographs dedicated to the Collaborative Research Center's main focus of research - that is, the materiality and presence of writing in non-typographic societies.